Melastomataceae juss. na Serra dos Pireneus, estado de Goiás: diversidade e comparação florística - Versiane, Ana Flávia Alves (2014)
The present study provides a survey of the Melastomataceae from Serra dos Pireneus which was done in two chapters. Chapter I entitled \"The Melastomataceae flora from Serra dos Pireneus, Goiás state: diversity analysis and floristic similarity \" presents a comparative analysis of the species of Melastomataceae from Serra dos Pireneus with 17 areas of similar physiognomies from Bahia, Goiás, Minas Gerais and São Paulo states. Chapter II entitled Melastomataceae Juss. from Serra dos Pireneus, Goiás state, Brazil presents thesystematic treatment of 78 species cataloged in the Serra dos Pireneus. All Melastomataceae collections from Serra dos Pireneus deposited in the CEN, ESA, HUEG, HUFU, IBGE, MBM, RB, SP, UB, UEC and UFG herbaria were analysed, determined or confirmed. From April 2012 to May 2013 six expeditions to Serra dos Pireneus were realised. All collections are deposited in HUFU herbarium and duplicates will be send to HUEG and UFG herbaria. Miconia is the most diverse genus with 19 species, followed by Tibouchina with 13 species and Microlicia with 12 species. Leandra is represented by five species, Siphanthera by four species, Clidemia, Pterolepis and Trembleya have three species each, Acisanthera, Cambessedesia, Lavoisiera and Rhynchanthera two species each and Chaetostoma, Comolia, Desmoscelis, Macairea, Ossaea, Poteranthera, Stenodon and Tococa one specie each. Chapter I provides a list of 78 species of Melastomataceae and 20 genera distributed in different vegetation physiognomies in the Serra dos Pireneus. The clustering analysis among 18 localities shows three groups: Minas Gerais group, Goiás (incl. São Paulo) group and Bahia group. The highest floristic similarity between 4 Serra dos Pireneus, Serra Dourada and Chapada dos Veadeiros can be explained by geo-climatic conditions and geographic distance. The lowest similarity occurs with Mucugê, Bahia state. Chapter II provides identification keys for genera and species as well as descriptions, geographical data, taxonomic comments and illustrations of diagnostic characters. Melastomataceae is an important floristic component in the Serra dos Pireneus, and five endemic species from Goiás occur in Pireneus.